LO59: Police use of force and subsequent emergency department assessment-mental health concerns are the driving force behind ED use and choice of transport mode. (15th May 2017) - Hall, C.A.; Votova, K.; Eramian, D.; MacDonald, S.; Heyd, C.G.; Sedgwick, C.
Abstract : Introduction: We examined persons transported to hospital after police use of force to determine whether Emergency Department (ED) assessment and/or mode of transport could be predicted.Methods: A multi-site prospective consecutive cohort study of police use of force with data on ED assessment for individuals ≥18 yrs was conducted over 36 months (Jan 2010-Dec 2012) in 4 cities in Canada. Police, EMS and hospital data were linked by study ID. Stepwise logistic regression examined the relationship between the police call for service and subject characteristics on subsequent ED assessment and mode of transport.Results: In 3310 use of force events, 86.7% of subjects were male, median age 29 yrs. ED transport occurred in 26% (n=726). Odds of ED assessment increased by 1.2 (CI 1.1, 1.3) for each force modality >1. Other predictors of ED use: if the nature of police call was for Mental Health Act (MHA) (Odds 14.3, CI 10.6, 19.2), features of excited delirium (ExD) (Odds 2.7, CI 1.9, 3.7), police-assessed emotional distress (EDP) not an MHA (Odds 2.1, CI 1.5, 3.0) and combined drugs, alcohol and EDP (Odds 1.7, CI 1.9, 3.7). Those with alcohol impairment alone were less likely to go to ED from the scene: OR 0.6 (CI 0.5, 0.7). EMS transported 55% of all patients (n=401), although police transported ~100 people who EMS attended at the scene but did not subsequently transport. For patients brought to the ED, 70% had a retrievable chart (512/726) with a discernible primary diagnosis: 25% for physical injury, 32% for psychiatric and 43% for drug and/or alcohol intoxication. For use of force events that began as MHA calls, patient transport was more often by police car than ambulance OR 1.8 (CI 1.2, 2.5), while those with drug intoxication or ≥3 ExD features were more often brought by ambulance: odds of police transport 0.5 (CI 0.3, 0.9) and 0.4 (CI 0.3, 0.7). Violence or aggression did not predict mode of transport in our study.Conclusion: About one quarter of police use of force events lead to ED assessment; 1 in 4 patients transported had a physical injury of some description. Calls including the Mental Health Act or individuals with drug intoxication or excited delirium features are most predictive of ED use following police use of force. In MHA calls with use of force, persons are nearly twice as likely to go to ED by police car than by ambulance.